I told'em exactly (London : Video Arts, 1975)
In this light hearted animated feature, short, fast-talking foreman Mitt Mittel knows his job, but not how to communicate with the bosses aboveor the workers below. Before and after viewing, questions help fasilitate a discussion of the dynamics presented and how such problems might be avoided
Keywords: Communication in personnel management